Evaluation of the toxicity of azo dyes by Allium cepa and study to remove these compounds in aqueous solution by Saccharomyces cerevisiae - de Almeida, Érica Janaina Rodrigues [UNESP]; Dilarri, Guilherme [UNESP]; Corso, Carlos Renato [UNESP] (Springer Nature, 2018)
Textile industries are among the largest consumers of synthetic azo dyes. The effluents generated by them, especially during the dyeing stage of tissues, present high staining and concentration of organic loads. The disposal of azo dyes in the environment represents one of the main environmental problems, due to its high pollution potential. The recalcitrance from these compounds is due to the complexity of their molecular structures, which have a large number of aromatic rings, azo bonds, amines, amides, phenolic, and sulfonic groups. Their degradation is difficult and harmful to the organisms exposed to them. Several types of research aim to find treatments that are able to reduce the concentration of these compounds and, consequently, the metabolites that are generated from their degradation. Those treatments can often become more toxic than the initial molecule. Among these treatments, biological treatment has a prominent place because they present good efficiency and lower costs for its implantation. Thus, this paper aimed to study the toxicity of the synthetic azo dyes Acid Orange 7 and Direct Violet 51 using as test organism bulbs of Allium cepa. The toxicity of these compounds was evaluated before and after degradation treatment with Saccharomyces cerevisiae. One of the main concerns of the study was to use simple methods of analysis, so bulbs of A. cepa were chosen to evaluate the toxicity, and yeast S. cerevisiae to carry out the process of decolorization.
Keywords: Acid Orange 7; Allium cepa; Direct violet 51; Saccharomyces cerevisiae